Microphysical and radiative characterization of a subvisible midlevel Arctic ice cluod by airborne observations - a case study - Lampert, A.; Ehrlich, A.; Dörnbrack, A.; Jourdan, O.; Gayet, J.-F.; Mioche, G.; Shcherbakov, V.; Ritter, C.; Wendisch, M. (Atmospheric Chemistry and Physics, 2009)
During the Arctic Study of Tropospheric Aerosol, Clouds and Radiation (ASTAR) campaign, which was conducted in March and April 2007, an optically thin ice cloud was observed south of Svalbard at around 3 km altitude. The microphysical and radiative properties of this particular subvisible midlevel cloud were investigated with complementary remote sensing and in situ instruments. Collocated airborne lidar remote sensing and spectral solar radiation measurements were performed at a flight altitude of 2300 m below the cloud base. Under almost stationary atmospheric conditions, the same subvisible midlevel cloud was probed with various in situ sensors roughly 30 min later. From individual ice crystal samples detected with the Cloud Particle Imager and the ensemble of particles measured with the Polar Nephelometer, microphysical properties were retrieved with a bi-modal inversion algorithm. The best agreement with the measurements was obtained for small ice spheres and deeply rough hexagonal ice crystals. Furthermore, the single-scattering albedo, the scattering phase function as well as the volume extinction coefficient and the effective diameter of the crystal population were determined. A lidar ratio of 21(ÃÂ±6) sr was deduced by three independent methods. These parameters in conjunction with the cloud optical thickness obtained from the lidar measurements were used to compute spectral and broadband radiances and irradiances with a radiative transfer code. The simulated results agreed with the observed spectral downwelling radiance within the range given by the measurement uncertainty. Furthermore, the broadband radiative simulations estimated a net (solar plus thermal infrared) radiative forcing of the subvisible midlevel ice cloud of Ã¢ÂÂ0.4 W mÃ¢ÂÂ2 (Ã¢ÂÂ3.2 W mÃ¢ÂÂ2 in the solar and +2.8 W mÃ¢ÂÂ2 in the thermal infrared wavelength range).